A Collaborative Effort to Establish a Convalescent Plasma Program in South Florida - Roberto L. Roman Laporte; Edwina Brathwaite (Library & Knowledge Services and Nursing & Health Sciences Research Departments, 2020)
On March 11, 2020, Miami-Dade County had its first diagnosed case of COVID-19 and quickly became the top hotspot of COVID-19 cases in Florida. Hospitals were challenged to find effective treatments to combat the virus. A collaborative effort between Doctors Hospital and Boca Raton Regional Hospital established a robust convalescent plasma program for critically ill patients diagnosed with COVID-19 within Baptist Health South Florida.